Periaqueductal grey cyclooxygenase-dependent facilitation of C-nociceptive drive and encoding in dorsal horn neurons in the rat - Leith, J.L.; Wilson, Alex W.; You, Hao-Jun; Lumb, Bridget M.; Donaldson, Lucy F. (Wiley, 2014)
The experience of pain is strongly affected by descending control systems originating in the brainstem ventrolateral periaqueductal grey (VL-PAG), which control the spinal processing of nociceptive information. A- and C-fibre nociceptors detect noxious stimulation, and have distinct and independent contributions to both the perception of pain quality (fast and slow pain, respectively) and the development of chronic pain. Evidence suggests a separation in the central processing of information arising from A- vs. C-nociceptors; for example, inhibition of the cyclooxygenase-1 (COX-1)–prostaglandin system within the VL-PAG alters spinal nociceptive reflexes evoked by C-nociceptor input in vivo via descending pathways, leaving A-nociceptor-evoked reflexes largely unaffected. As the spinal neuronal mechanisms underlying these different responses remain unknown, we determined the effect of inhibition of VL-PAG COX-1 on dorsal horn wide dynamic-range neurons evoked by C- vs. A-nociceptor activation. Inhibition of VL-PAG COX-1 in anaesthetised rats increased firing thresholds of lamina IV–V wide dynamic-range dorsal horn neurons in response to both A- and C-nociceptor stimulation. Importantly, wide dynamic-range dorsal horn neurons continued to faithfully encode A-nociceptive information, even after VL-PAG COX-1 inhibition, whereas the encoding of C-nociceptor information by wide dynamic-range spinal neurons was significantly disrupted. Dorsal horn neurons with stronger C-nociceptor input were affected by COX-1 inhibition to a greater extent than those with weak C-fibre input. These data show that the gain and contrast of C-nociceptive information processed in individual wide dynamic-range dorsal horn neurons is modulated by prostanergic descending control mechanisms in the VL-PAG.